The devil's hand : a thriller - Carr, Jack (Joint pseudonym) (New York : Pocket Books, 2021)
Former Navy SEAL James Reece is entrusted with a top-secret CIA mission of retribution twenty years in the making. Halfway across the globe a regional superpower struggles with sanctions imposed by the United States and her European allies, a country whose ancient religion spawned a group of ruthless assassins. Faced with internal dissent and extrajudicial targeted killings by the United States and Israel, the Supreme Leader puts a plan in motion to defeat the most powerful nation on earth.
Includes an excerpt from In the blood.
Includes biographical references.
Keywords: Reece, James -- (Fictitious character) -- Fiction; United States. -- Navy. -- SEALs -- Fiction; Terrorism -- Fiction; Biological weapons -- Fiction; Terrorism -- Prevention -- Fiction; Veterans -- Fiction; Political fiction; Thrillers (Fiction); Action and adventure fiction